Polycomb EZH1 regulates cell cycle/5‐fluorouracil sensitivity of neuroblastoma cells in concert with MYCN. Issue 12 (7th October 2022) - Shinno, Yoshitaka; Takenobu, Hisanori; Sugino, Ryuichi P.; Endo, Yuki; Okada, Ryu; Haruta, Masayuki; Satoh, Shunpei; Mukae, Kyosuke; Shaliman, Dilibaerguli; Wada, Tomoko; Akter, Jesmin; Ando, Kiyohiro; et al.
Abstract: In the present study, we found that EZH1 depletion in MYCN ‐amplified neuroblastoma cells resulted in significant cell death as well as xenograft inhibition. EZH1 depletion decreased the level of H3K27me1; the interaction and protein stabilization of MYCN and EZH1 appear to play roles in epigenetic transcriptional regulation. Transcriptome analysis of EZH1‐depleted cells resulted in downregulation of the cell cycle progression‐related pathway. In particular, Gene Set Enrichment Analysis revealed downregulation of reactome E2F‐mediated regulation of DNA replication along with key genes of this process, TYMS, POLA2, and CCNA1 . TYMS and POLA2 were transcriptionally activated by MYCN and EZH1‐related epigenetic modification. Treatment with the EZH1/2 inhibitor UNC1999 also induced cell death, decreased H3K27 methylation, and reduced the levels of TYMS in neuroblastoma cells. Previous reports indicated neuroblastoma cells are resistant to 5‐fluorouracil (5‐FU) and TYMS (encoding thymidylate synthetase) has been considered the primary site of action for folate analogues. Intriguingly, UNC1999 treatment significantly sensitized MYCN‐amplified neuroblastoma cells to 5‐FU treatment, suggesting that EZH inhibition could be an effective strategy for development of a new epigenetic treatment for neuroblastoma. Abstract : EZH1 depletion in MYCN‐amplified neuroblastoma cells resulted in significant cell death as well as xenograft inhibition. TYMS and POLA2 were transcriptionally activated by MYCN and EZH1‐related epigenetic modification. EZH inhibitor UNC1999 treatment significantly sensitized MYCN‐amplified neuroblastoma cells to 5‐FU treatment.